Exploring Multifaith Education : Bridging Gaps in Global Religious Understanding - Angga Widyantara; Aprilita Rizki Wulandari; Audi Faundra Firmansyah (International Forum of Researchers and Lecturers, 2024)
Multifaith education has become an essential tool for promoting mutual understanding and coexistence in today’s increasingly pluralistic societies. This article examines the impact of multifaith education programs on fostering tolerance and empathy among students of diverse religious backgrounds. It explores case studies from different countries and provides practical strategies for educators to incorporate multifaith principles into their teaching practices. The findings underscore the transformative potential of religious education in bridging cultural and spiritual divides.